Moisture in the soil profile with water applications using pulse drip irrigation - Maller, André; Rezende, Roberto; Freitas, Paulo Sérgio; Seron, Cassio; Hachmann, Tiago (Revista Ciência Agronômica, 2019)
The wet bulb is the volume that presents greater moisture in relation to the initial soil moisture, being a result of local application of irrigation water. Due to increased moisture in the soil, successive irrigation events tend to form bigger wet bulbs and superficial water accumulation area (SWAA). The objective was to verify the distribution of water in the soil profile, with intermittent application of water, considering the hypothesis that moisture increase prior to the application of the water pulse changes the characteristics of the wet bulb, and to evaluate the effect of increasing SWAA on the lateral dimensions of the bulb. The water applications were performed using 1, 2 and 4 pulses in the flows of 4 and 8 L h-1, totalizing six treatments, which were carried out in four replications for each treatment. The evaluations of SWAA were performed with the continuous application of water at the mentioned flow rates. It was observed that the changes in moisture distribution within the wet bulb due to intermittent application of water and the magnitude of the SWAA are ephemeral.